3D FE modelling of machining forces during AISI 4140 hard turning - Tzotzis, Anastasios (Strojniški vestnik, 2020)
Hard turning is one of the most used machining processes in industrial applications. This paper researches critical aspects that influence the machining process of AISI 4140 to develop a prediction model for the resultant machining force-induced during AISI 4140 hard turning, based on finite element (FE) modelling. A total of 27 turning simulation runs were carried out in order to investigate the relationship between three key parameters (cutting speed, feed rate, and depth of cut) and their effect on machining force components. The acquired numerical results were compared to experimental ones for verification purposes. Additionally, a mathematical model was established according to statistical methodologies such as the response surface methodology (RSM) and the analysis of variance (ANOVA). The plurality of the simulations yielded results in high conformity with the experimental values of the main machining force and its components. Specifically, the resultant cutting force agreement exceeded 90 % in many tests. Moreover, the verification of the adequacy of the statistical model led to an accuracy of 8.8 %.
Keywords: 3D-analiza po metodi končnih elementov; 3-dimensional finite element modelling; AISI 4140 turning; machining forces; metodologija odzivne površine; response surface methodology; sile pri obdelavi; struženje AISI 4140